THE RESILIENCE DIVIDEND: HOW POST-CRISIS HR PRACTICES SHAPE ORGANIZATIONAL LEARNING AND ADAPTIVE CAPABILITY - Amalia Susanti; Ramon Zamora; Oktavianti (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
The increasing frequency of organizational crises has highlighted the importance of resilience as a critical capability for sustaining performance in uncertain environments. This study introduces the concept of the “resilience dividend,” which refers to the long-term benefits organizations can derive from effectively managing and learning from crises. Drawing on a conceptual and qualitative review of literature on human resource management, organizational resilience, and learning, the paper examines how post-crisis HR practices contribute to organizational learning and the development of adaptive capability. Key practices such as talent retention and redeployment, employee well-being initiatives, flexible work arrangements, and continuous learning are identified as central to this process. The findings suggest that organizations that move beyond short-term recovery and focus on institutionalizing learning are better positioned to enhance adaptability and long-term performance. The study also highlights the role of leadership and organizational culture in supporting these processes. A conceptual framework is proposed to illustrate the relationship between crisis experiences, HR interventions, and resilience outcomes. The paper contributes to HRM and resilience literature by offering an integrated perspective on post-crisis capability building. It concludes that organizations can achieve sustainable competitive advantage by leveraging the resilience dividend through strategic HR practices.